Exploring Price Trends and Market Integration of Coconut and Groundnut in Indian Oilseed Markets - Gowri Shankar; A. Malaisamy (Journal of the Indian Society of Agricultural Statistics, 2025)
Among the oilseed crops, Groundnut and Coconut prices are more unstable due to seasonality of production, perishable nature, production uncertainty etc. Lack of information on potential market as well as arrival and price behaviour of these oilseeds further worsen this situation of its growers. Since market integration helps in achieving price consistency and thus lead to marketing system efficiency, the present study examines the Market Integration of major oilseed crops–Coconut, and Groundnut–in India during the period of January 2013 to January 2024markets using Johansen’s cointegration test and Granger Causality test. In this study to test the stationarity of the price series Augmented Dickey Fuller test was used. The outcomes of the study strongly supported the presence of co-integration and interdependence of the selected markets from the result of Johansen cointegration test and Market integration analysis across intrastate and interstate regions identified causal relationships, such as unidirectional causality between certain regions for Coconut and bidirectional causality for Groundnut. The study stressed the need for systematic research to address production constraints, technical advancements, and policy influences, to manage emerging challenges effectively.